2011
DOI: 10.1371/journal.pone.0024002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Stimulation-Related Physiological Artifacts in Hemodynamic Near-Infrared Spectroscopy Signals

Abstract: Hemodynamic responses evoked by transcranial magnetic stimulation (TMS) can be measured with near-infrared spectroscopy (NIRS). This study demonstrates that cerebral neuronal activity is not their sole contributor. We compared bilateral NIRS responses following brain stimulation to those from the shoulders evoked by shoulder stimulation and contrasted them with changes in circulatory parameters. The left primary motor cortex of ten subjects was stimulated with 8-s repetitive TMS trains at 0.5, 1, and 2 Hz at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…In addition, the ANS has been increasingly used as an outcome measure in NIBS studies in order to understand the broad effects of these techniques including their safety profile. However, while there is clear evidence of autonomic effects of brain stimulation on animals (Yasui et al, 1991;Sequeira et al, 1995;Tavares et al, 2004), recent articles found conflicting results on the relationship of NIBS and ANS (Lai et al, 2010;Näsi et al, 2011;Vandermeeren et al, 2010;Brunoni et al, 2013). Therefore, it is important to consider the two-way relationship between central modulation and ANS function that can be used to explore both NIBS mechanisms and ANS function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ANS has been increasingly used as an outcome measure in NIBS studies in order to understand the broad effects of these techniques including their safety profile. However, while there is clear evidence of autonomic effects of brain stimulation on animals (Yasui et al, 1991;Sequeira et al, 1995;Tavares et al, 2004), recent articles found conflicting results on the relationship of NIBS and ANS (Lai et al, 2010;Näsi et al, 2011;Vandermeeren et al, 2010;Brunoni et al, 2013). Therefore, it is important to consider the two-way relationship between central modulation and ANS function that can be used to explore both NIBS mechanisms and ANS function.…”
Section: Introductionmentioning
confidence: 99%
“…A second approach for designing a concurrent TMS-optical montage is to reorient optodes so that they may be mounted in a low-profile optical patch directly beneath a TMS coil (Figure 2B). Creating a low-profile optical montage can be accomplished either by bending optodes, reorienting their tips at a perpendicular angle (Figure 2C; Noguchi et al, 2003; Mochizuki et al, 2006) or by using prisms to redirect light at a perpendicular angle (Figure 2C; Näsi et al, 2011; Parks et al, 2012). The advantage of the low-profile approach is that a montage may be designed with freedom, arranging optodes in any desired configuration.…”
Section: Design Considerations For Tms-fnirs and Tms-erosmentioning
confidence: 99%
“…However, TMS induces electrical currents not only in the neural tissue of the cerebral cortex but also in superficial tissue, musculature, and nerves of the scalp and skull. Thus, TMS-induced changes in near-infrared absorption and scattering may also occur in superficial tissue, including changes in superficial blood flow and oxygenation (Figure 3C) (Näsi et al, 2011). Such superficial tissue artifacts , if present, are not easily disentangled from cortical activations and present the greatest challenge for combined TMS and optical imaging experiments (Näsi et al, 2011).…”
Section: Potential Artifacts In Tms-fnirs and Tms-erosmentioning
confidence: 99%
See 2 more Smart Citations